Skaitmeninimo stebėsenos sistemos koncepcinis modelis: Lietuvos patirtis - Varnienė-Janssen, Regina; Juškys, Jonas; Račkauskaitė, Neringa (Information & Media, 2013)
Siekiant padidinti skaitmeninimo veiklų valdymo efektyvumą, Lietuvos kultūros paveldo skaitmeninimo, skaitmeninio turinio saugojimo ir prieigos strategijoje (2009–2013) buvo numatyta sukurti kultūros paveldo skaitmeninimo stebėsenos sistemą ir nuolat vykdyti Lietuvos kultūros paveldo skaitmeninio stebėsenąbei vertinimą. Straipsnyje supažindinama su skaitmeninimo stebėsenos sistemos koncepciniu modeliu, grindžiamu pagrindiniais sistemų teorijos principais bei sisteminiu požiūriu paremta vertinimo teorija. Koncepcinis modelis integruoja skaitmeninimo stebėsenos sistemos apibrėžties ir jos paskirties aprašymą, modelio kūrimo principus ir metodologiją, stebėsenos rodiklių pasirinkimą bei jų aprobavimo rezultatus.Pagrindiniai žodžiai: koncepcinis modelis, metodologija, stebėsenos rodikliai, skaitmeninimas, skaitmeninimo stebėsenos sistema.A conceptual model of the digitization monitoring system: the Lithuanian experienceRegina Varnienė-Janssen, Jonas Juškys, Neringa RačkauskaitėSummary The article presents a conceptual model for a digitization monitoring system, which will be used as the basis for implementing a digitization monitoring system in Lithuania. The conceptual model, which is based on the systems theory and evaluation theory principles, involves the description of the digitization monitoring system and its scope, principles for the creation of the model, and the choice of the monitoring indicators and their approbation results. The key factor influencing the creation of such a system is digitization performed by numerous independent institutions subordinate to different ministries. The creation of a system for monitoring the digitization of cultural heritage objects aims at preventing the duplication of digitization activities, ensuring an effective use of technical equipment and software for performing the digitization of cultural heritage objects, applying the best practice of coordinated digitization activities and appropriate standards and formats, as well as a convenient and prompt access to information and statistical data on the results of the activities being performed. The digitization monitoring system is created in line with recommendations of the Feasibility Study for the Creation of a Digitization Monitoring System, prepared on demand of the Martynas Mažvydas National Library of Lithuania, and requirements of the Specification for the Creation of Software for a Digitization Monitoring System in which, as one of its main requirements, was the creation of a manual of digitization monitoring. The article builds on the above-mentioned feasibility study. The rationale for the creation of a digitization monitoring system conforms with this system’s theory principles which require that the modelling of a system activities should involve an analysis of the input, process, and output, as well as feedback evaluation. The conceptual model of digitization monitoring is based on the following principles:• the system’s activity is shaped and organized by a holistic evaluation of the existing approaches to the creation of such systems; realization that a system aggregates multiple elements (interacting institutions and their units) which interact among themselves and with the environment; and abstraction of all elements and their interactions and merging them into a conceptual model.• indicators within a digitization monitoring system are determined through defining the existing state and problems of digitization activities, investigating the monitoring demands and requirements for such systems, and evaluating the conceptual model of this system, based on the results of a discussion.• The main criteria for selecting the indicators of digitization monitoring are clarity, relevance, efficiency, and possibility to monitor. A conceptual model based on the holistic approach allows designing a system able to monitor digitization activity results, standards and formats of metadata and access, identification and distribution of tasks, and tracking implementation of goals. It also enables institutions performing digitization activities to acquire information on digitization initiatives and current and (or) intended projects, on resources held by other institutions and the characteristics of these resources, on trainings, conferences or other events related to digitization that are on the agenda, also, it enables to successfully monitor and keep under review the realization of initiatives, programmes, and strategies, to facilitate a quality evaluation and performance improvement, to assess the risks, to improve supervision activities, efficiency, and management processes, to prepare accounts, to substantiate resources and expenses, to increase performance impact, and to monitor digitization initiatives as well as current and (or) intended projects.